2022
DOI: 10.3390/ma15061983
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Characteristics and Luminescent Properties of Natural Fluorite with Three Different Colors

Abstract: Fluorite is rich in mineral resources and its gorgeous colors and excellent luminescence characteristics have attracted the attention of many scholars. In this paper, the composition, structure, luminescent properties, and the potential application value of three fluorites with different colors and are systematically analyzed. The results show that REE and radioactive elements have effects on the structure, color, and luminescence of fluorite. Radioactive elements Th and U will aggravate the formation of cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(74 reference statements)
1
2
0
Order By: Relevance
“…3. In this gure, a distinctive Raman peak is consistently observed for all samples from different areas, appearing at approximately 322 cm ¹ [17]. This observation aligns with the uorite peak documented in the RRUFF database (ID: R050046).…”
Section: Raman Spectroscopysupporting
confidence: 86%
See 2 more Smart Citations
“…3. In this gure, a distinctive Raman peak is consistently observed for all samples from different areas, appearing at approximately 322 cm ¹ [17]. This observation aligns with the uorite peak documented in the RRUFF database (ID: R050046).…”
Section: Raman Spectroscopysupporting
confidence: 86%
“…Lewandowski et al [21] observed Raman peak at 319.13 cm − 1 for calcium uoride. This speci c peak at around 320-322 cm ¹ is attributed to the T 2g Raman active vibrational mode of uorite [17], [22][23][24][25][26]. It's worth noting that white uorite typically exhibits a single Raman peak at around 320 cm ¹, while non-white uorite may display additional peaks at different locations [19].…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation